2019
DOI: 10.5114/pjr.2019.90370
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of myocardial bridging on multidetector computed tomography and its relation to coronary plaques

Abstract: Purpose: To test the hypothesis that the prevalence of myocardial bridging varies between ethnic groups, and that the segment proximal to the myocardial bridge is more prone to plaque formation. Material and methods:A total of 4500 patients who had undergone computerised tomography (CT) coronary angiography at our institute were studied for myocardial bridging. Data on the clinical profile and indication for CT coronary angiography in myocardial bridging were collected. Patients with and without proximal disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 21 publications
1
6
1
4
Order By: Relevance
“…10 A recent study including 4500 patients who had undergone CCTA found the prevalence of myocardial bridging to be 10%. 11 The present study detected bridging in 17 patients yielding a rate of 10%. The prevalence of anomalous coronary arteries in the general population has been reported to be 1.5% as detected by magnet resonance imaging and 2.6% as detected by CCTA.…”
Section: Discussionsupporting
confidence: 46%
“…10 A recent study including 4500 patients who had undergone CCTA found the prevalence of myocardial bridging to be 10%. 11 The present study detected bridging in 17 patients yielding a rate of 10%. The prevalence of anomalous coronary arteries in the general population has been reported to be 1.5% as detected by magnet resonance imaging and 2.6% as detected by CCTA.…”
Section: Discussionsupporting
confidence: 46%
“…In recent years, it has been found that the myocardial bridge is closely related to a variety of clinical cardiovascular diseases. The myocardial bridge exerts compression on coronary artery, especially during systole, which can compress parietal coronary artery and cause angina pectoris, myocardial infarction, ventricular dysfunction, arrhythmia, and other symptoms [ 7 ]. However, because most patients with the myocardial bridge have no obvious clinical symptoms, they are often ignored by clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding anatomical location, 67 to 98% of MBs are located in the ADA, most frequently in its proximal and middle segments. The Cx and RCA are affected less often 31,32 . Keeping in mind the high rate of MBs detected on autopsy, coronary computed tomography angiography is considered to be the most sensitive modality, compared with invasive coronary angiography and intravascular imaging, for general diagnostic purposes.…”
Section: Course Anomaliesmentioning
confidence: 99%